2011
DOI: 10.1007/s11606-011-1915-2
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation Interventions for Patients with Depression: A Systematic Review and Meta-analysis

Abstract: OBJECTIVES:We conducted a systematic literature review of smoking cessation interventions for patients with histories of depressive disorders or current significant depressive symptoms. We examined the comparative effectiveness of smoking cessation strategies on abstinence rates, differential effects of cessation strategies by depression status (i.e., history positive vs. current depression), and differential effects by gender. DATA SOURCES: Peer-reviewed literature in MEDLINE, Embase, PsycINFO, and Cochrane L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 55 publications
4
78
2
3
Order By: Relevance
“…It may be beneficial to target these aspects of smoking when developing and administering pharmacological and behavioral smoking cessation services to adults with depression. In addition, smoking interventions that include mood management components improve quit outcomes compared to standard interventions (83,84) suggesting the importance of addressing depressive symptoms during smoking cessation efforts.…”
Section: Discussionmentioning
confidence: 99%
“…It may be beneficial to target these aspects of smoking when developing and administering pharmacological and behavioral smoking cessation services to adults with depression. In addition, smoking interventions that include mood management components improve quit outcomes compared to standard interventions (83,84) suggesting the importance of addressing depressive symptoms during smoking cessation efforts.…”
Section: Discussionmentioning
confidence: 99%
“…46 A systematic review 47 of 49 randomized controlled trials examining smoking cessation outcomes in smokers with past or current depression found that adding a psychosocial mood management component to a standard smoking cessation intervention, compared with standard smoking cessation alone, increases cessation rates for smokers with current or past depression. In addition, a recent review 48 found that including a behavioral mood management component as well as nicotine replacement therapy has a small, beneficial effect on depressed smokers' ability to quit. These findings suggest that smokers with past or current depression are capable of quitting and may benefit from the development of treatments specifically tailored to their dual diagnosis.…”
Section: Outcomes Of Smoking Cessation Therapy In Depressed Smokersmentioning
confidence: 99%
“…In line with this reasoning, light smokers who described using cigarettes as antidepressants or prop for moral support would understandably be more likely to relapse, especially women (Weinberger et al, 2012). A more intensive follow-up combining cessation counselling with psychological support or negative affect management may facilitate cessation among light smokers presenting with an anxio-depressive profile (Blalock et al, 2008;Gierisch et al, 2012;Weinberger et al, 2012).…”
Section: Discussionmentioning
confidence: 94%